Report on Bangladesh characterization study - Fish production baseline at country level - Rossignoli, Cristiano; Dam Lam, Rodolfo; Brako Dompreh, Eric; Gasparatos, Alexandros; Lozano, Denise; Manyise, Timothy; Paz Mendez, Alvaro (WorldFish, 2022)
Characterisation study at country level (Bangladesh): Executive summary and initial findings.